PERANCANGAN BANGUNAN SEKOLAH LUAR BIASA TUNARUNGU DENGAN PENDEKATAN DEAFSPACE GUIDELINES - , LIANA DWI ARIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The quality of education for the disabled is still below standard and need a lot of improvement. One way to improve the quality of education is disabled by means of proper school buildings. Physical school building that accommodated activities that affect the learning activities. Nowadays, schools for disabled providing services to a wide range of disabilities, although there are some that provide intensive care for a disabled category. Each category of disability has different characteristics that require special handling. Given this special handling, students with disabilities can develop more optimal in terms of education. Deafspace guideline is an alternative reference for creating a comfortable learning place for students with hearing impairment. In deafspace guidelines, spatial aspects, materials, acoustics and light considered to be in accordance with the character of the user that is deaf. Aperture space considerations need to improve or even limiting visual range according to the needs of the space. Some vibration zone with wood floors help increase the sensitivity of users to other users. Deafspace guidelines appropriate design to optimize the senses of vision and ability to feel vibrations by the deaf in recognizing space and activities in it.